Academic Senate Minutes 2005-09-15 - Academic Senate:::::::::
Report of the Chair. Special Report: SSU's response to Rohnert Park's University District. Agenda approved. Minutes of 9/1/05 approved. Update on WASC. Periodic Review of Administrators postponed. Reports from President, Provost, Executive VP of Asssociated Students, EPC, FSAC and SAC. Good of the Order.